Students' acceptance and use of e-learning tool: a case study on the use of Edmodo at Kolej Professional Mara Seri Iskandar / Noor Faizah Sidek - Sidek, Noor Faizah (2016)
E-learning is now an established presence within the global higher education industry. Demand on e-learning courses increased as it offers flexibility in learning. This study aims to identify the usage pattern of Edmodo among the students, to identify the factors that influence the students' acceptance on the usage of Edmodo and to the barriers faced by the students in using Edmodo at Kolej Profesional MARA Seri Iskandar. Five variables have been determined in the research model which is formulated from the Unified Theory of Acceptance and Use of Technology (UTAUT). The five variables are performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC) and the behavioural intention to use (BI). Data from 310 respondents was collected by using a questionnaire and was analysed using the SPSS descriptive and inferential analysis techniques. Results show the usage pattern among the students are at high end, though there are rooms for improvement. Senior students which have more experiences in using Edmodo have the highest usage percentage across all functions. However, there are numbers of students who have never use the functions in Edmodo with the highest of 37.8% students have never respond to their friends' posting. In contrast, the most used functions are downloading notes from lecturer (20.7%) and execute assessments (20.8%). The highest rated barriers are feeling upset in solving exercises and activities, low bandwidth and lack of computer lab that offers open access in the college. The study should involves more respondents and done in a longitudinal way as the results may change over time.